Comparative genomics of infective Saccharomyces cerevisiae strains reveals their food origin - Miguel Morard; Laura Pérez-Través; Carla Perpiñá; María Lairón-Peris; María Carmen Collado; Roberto Pérez-Torrado; Amparo Querol (Scientific Reports, 2023)
Abstract Fungal infections are less studied than viral or bacterial infections and often more difficult to treat. Saccharomyces cerevisiae is usually identified as an innocuous human-friendly yeast; however, this yeast can be responsible for infections mainly in immunosuppressed individuals. S. cerevisiae is a relevant organism widely used in the food industry. Therefore, the study of food yeasts as the source of clinical infection is becoming a pivotal question for food safety. In this study, we demonstrate that S. cerevisiae strains cause infections to spread mostly from food environments. Phylogenetic analysis, genome structure analysis, and phenotypic characterization showed that the key sources of the infective strains are food products, such as bread and probiotic supplements. We observed that the adaptation to host infection can drive important phenotypic and genomic changes in these strains that could be good markers to determine the source of infection. These conclusions add pivotal evidence to reinforce the need for surveillance of food-related S. cerevisiae strains as potential opportunistic pathogens.